Women in management: Underrepresented and overstretched? - Biletta, Isabella; Mullan, Jack; Parent-Thirion, Agnès; Wilkens, Mathijn (Luxembourg, 2018)
"Despite years of gender equality legislation, men outnumber women in management positions by two to one. While structural barriers continue to impede women’s career advancement, women themselves may be deterred from becoming managers if they perceive that it would have a negative impact on their working and personal lives. What is the experience of women in management roles and how can their underrepresentation in management be addressed? These are the questions this policy brief seeks to answer by looking at the job quality of managers, both female and male, and the impact a management job has on personal life."